Street milk and urban consumers in Turkey: A descriptive study - Konar, Nevzat; Kaya, Iraz Haspolat; Dalabasmaz, Sevim; Poyrazoglu, Ender Sinan; Artik, Nevzat (Journal of Consumer Protection and Food Safety, 2014)
Milk is important because of its composition, its consumption prevalence, and its use as a raw material for many food products. The milk's shelf life, reliability during processing, and quality conservation should be considered by the consumer. However, in Turkey, raw milk is sold unpackaged and untreated (by physical processes or heat treatment) by street suppliers without the use of any of the required food conservation techniques. This type of milk is generally called 'street milk' (SM). This study was conducted to analyse the Turkish urban consumers' (UCs) attitudes, behaviours, and perceptions with respect to SM. To achieve a 2.83 % sampling tolerance, 1222 consumers were interviewed in person, and the data were collected. Although 23.6 % of UCs prefer SM, the potential customer rate is 43.1-48.9 %. These UCs tend to choose SM because the product is perceived to be 'organic', 'pure', and 'natural' and because they are suspicious of packaged/processed milk. In this study, the socio-economic statuses (SES) and age differences were identified (P < 0.05), and it was found that the 45+ age group and the low SES group have more positive views about SM. Thus, these groups must be made aware of the differences between 'raw milk' and 'SM', as well as the safety risks of SM and the importance of the processing and storing of dairy products, including milk. © 2013 Bundesamt für Verbraucherschutz und Lebensmittelsicherheit (BVL).
Created from Fastlane, Scopus look-up
Keywords: Attitudes; Awareness; Consumer; Food safety; Street milk